PENGARUH PENATAUSAHAAN ASET TETAP, SISTEM PENGENDALIAN INTERNAL , DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN DI KOTA PALEMBANG: - - Nadysa Aulia; Rita Martini; Yevi Dwitayanti (Indonesian Journal of Applied Accounting and Finance, 2022)
The purpose of this study is to analyze the impact of fixed asset administration, government internal control systems, and human resource competencies on the quality of financial reports in the city of Palembang. This study uses the main data using a questionnaire distributed through 51 OPD Palembang city. The number of samples taken in this study amounted to 102 respondents. Samples were taken using probability sampling technique. Research data is processed using narrative statistics and multiple linear regression analysis through the help of Statistical Products and Provider Solutions (SPSS) software. as a result of the research conducted shows that partially permanent asset administration has no effect on the quality of the Palembang city government's financial statements, the government's internal control system has a partial effect on the quality of the Palembang city government's financial statements, the competence of human resources has no partial effect on the quality of the Palembang city government's financial statements. Permanent Assets Administration does not have a positive impact on the Quality of Financial Statements, the Government's Inner Control System has a positive impact on the Quality of Financial Statements, Competence of Human Resources has no positive effect on the Quality of Financial Statements.